PENGARUH MODEL PEMBELAJARAN DRILL TERHADAP KEMAMPUAN BERTHAHARAH PESERTA DIDIK KELAS VII PADA MATA PELAJARAN FIKIH DI MTS BAHRUL ULUM NATAR - Ahmad Sirojul Islam; Jamal Fakhri; Rudy Irawan Z (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the low psychomotor abilities of students in practicing purification procedures due to the dominance of conventional Fiqh learning which tends to be oriented towards theoretical cognitive mastery alone. The focus of the problem in this research is directed at testing the effect of the drill learning model on the real improvement of thaharah abilities in grade VII students at MTs Bahrul Ulum Natar. Using a quantitative approach with a quasi-experimental design in the form of a pretest-posttest control group, this study involved the entire population of 49 students through a saturated sampling technique divided into experimental and control groups. Data were collected objectively using a performance test instrument for purification practices, classroom observations, and structured documentation analyzed using the SPSS program through the Independent Sample t-Test. The research findings prove that the experimental class experienced a significant increase in the average posttest score reaching 79.83 from the initial score of 61.25, surpassing the control class which only obtained a final score of 68.40. The results of the hypothesis test show a significance value of 0.000 less than 0.05 which means there is a real causal effect. The main conclusion of the study confirms that the application of the drill model through planned and repeated motor training has proven to be very effective in strengthening memory, accuracy of the sequence of pillars, and operational skills of ablution and tayamum worship of students in an applicable manner. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan psikomotorik peserta didik dalam mempraktikkan tata cara bersuci akibat dominasi pembelajaran Fikih konvensional yang cenderung berorientasi pada penguasaan kognitif teoritis belaka. Fokus masalah dalam riset ini diarahkan pada pengujian pengaruh model pembelajaran drill terhadap peningkatan kemampuan berthaharah secara nyata pada siswa kelas VII di MTs Bahrul Ulum Natar. Menggunakan pendekatan kuantitatif dengan desain eksperimen semu berbentuk pretest-posttest control group, studi ini melibatkan seluruh populasi sebanyak 49 peserta didik melalui teknik sampling jenuh yang terbagi menjadi kelompok eksperimen dan kontrol. Data dikumpulkan secara objektif menggunakan instrumen tes kinerja praktik bersuci, observasi kelas, serta dokumentasi terstruktur yang dianalisis menggunakan program SPSS melalui uji Independent Sample t-Test. Temuan riset membuktikan kelas eksperimen mengalami lonjakan nilai rata-rata posttest yang signifikan mencapai 79,83 dari nilai awal 61,25, melampaui kelas kontrol yang hanya memperoleh skor akhir sebesar 68,40. Hasil pengujian hipotesis menunjukkan nilai signifikansi 0,000 kurang dari 0,05 yang berarti terdapat pengaruh kausal yang nyata. Simpulan utama penelitian menegaskan bahwa penerapan model drill melalui latihan motorik yang terencana dan berulang terbukti sangat efektif dalam menguatkan daya ingat, ketelitian urutan rukun, serta keterampilan operasional ibadah wudhu dan tayamum peserta didik secara aplikatif.